Effect of fiber loading on the mechanical properties of bagasse fiber–reinforced polypropylene composites - Ali, Aidy; Subramonian, Sivarao; Amran, Mohammad; Dhar Malingam, Sivakumar; Salleh, Mohd Shukor; Raja Abdullah, Raja Izamshah (SAGE Publications Ltd., 2016)
It is evident that sugarcane/bagasse is a highly potential natural composite fiber. In this study, the correlation of composition fiber amount to the mechanical strength was presented. Bagasse was treated with alkali and then reinforced in polypropylene by means of hot pressing. Fiber loading was set to be varied from 10 to 20 wt%. Composite samples were subjected to tensile, hardness, and flexural characterization. Composites with 30 wt% of fiber loading registered maximum tensile strength while with 10 wt% fiber loading registered the minimum. Hardness increases with the amount of fiber. Flexural strength and flexural modulus were found to be greater than original polypropylene. Scanning electron microscopy examination revealed the mechanisms of the strength gain in morphological point of view. The findings give manufactures and engineers a sound basis decision whether to apply the use of this composite for weight reduction especially in automotive applications or not.